Who pays the taxes? - C. A. de Kam; J. de Haan; C. Giles; A. Manresa; E. Berenguer; S. Calonge; Joachim Merz (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1996)
The European Union is legally entitled to the revenue from (1) agricultural and sugar levies, (2) customs duties, (3) a 1 percent rate on each Member States' value added tax base, and (4) a resource on the basis of GNP. Currently, the Union is actively involved in the search for a fifth own revenue source. Therefore, the European Commission (DG XIX) has invited the authors to trace who pays the taxes. As requested, our report gives a general account of methods to investigate impacts of taxation. More specifically, we have estimated the incidence of national tax systems (Germany, the Netherlands, Spain and the United Kingdom), and the incidence of present own resources and prospective new (tax) resources of the European Union. Up till now, such information was not (readily) available. – – Der Europäischen Union werden gesetzlich folgende Einnahmearten zugeschrieben: (1) aus Agrarabschöpfungen, (2) aus Zöllen, (3) Mehrwertsteuer-Eigenmittel und (4) BSPEigenmittel. Gegenwärtig sucht die Europäische Union nach einer fünften Eigenmittelquelle. Daher hat die Europäische Kommission (DG XIX) die Autoren des vorliegenden Beitrags aufgefordert, zu der Frage 'Wer bezahlt die Steuern?' Stellung zu nehmen. Unser Bericht stellt zunächst einmal die Methoden zur Erforschung der Steuerwirkungen dar. Insbesondere haben wir das Aufkommen und die Verteilung nationaler Steuersysteme (Deutschland, Niederlande, Spanien und Großbritannien), der jetzigen EU-Eigenmittel und der zukünftigen Quellen der EU geschätzt. Bis jetzt waren Informationen dieser Art nicht direkt zugänglich.
Keywords: D30; D31; H24; 330; tax incidence in the European Union; prospective new EU tax resources; Steuerinzidenz in der Europäischen Gemeinschaft; neue EUSteuerressourcen